MODERATING ROLE OF BUSINESS AGE IN SMES’ COMPLIANCE WITH SAK ETAP FINANCIAL REPORTING - Hamzah, Amir; Suhendar, Dadang; Rahmasari, Sani; Sumarni, Nani (Indonesian Journal Of Business And Economics, 2024)
This study aims to analyze the factors influencing financial reporting in fashion SMEs in Kuningan Regency in relation to the application of SAK ETAP standards, with business age as a moderating variable. The research uses a quantitative approach with Partial Least Squares Structural Equation Modeling (SmartPLS), which enables the examination of relationships between variables as well as the moderation of business age. The sample consists of 120 respondents, who are owners or managers of fashion SMEs that have been operating for more than one year and have basic accounting knowledge. The results show that accounting understanding has a significant effect on financial reporting, while owner’s bookkeeping skills and business age do not have a significant direct impact. However, business age strengthens the effect of accounting understanding on financial reporting, indicating that the experience and stability of older businesses enhance the application of accounting principles. These findings provide insights for the development of policies and training programs to improve SMEs' compliance with financial reporting standards.Keywords: financial reporting, accounting understanding, owner’s bookkeeping skills, business age, SAK ETAP